2016
DOI: 10.1039/c6cp01926a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, photophysical, electrochemical and electrochemiluminescence properties of A2B2 zinc porphyrins: the effect of π-extended conjugation

Abstract: The synthesis of two A2B2 porphyrins, {5,15-bis-[4-(octyloxy)phenyl]-porphyrinato}zinc(ii) () and {5,15-bis-(carbazol-3-yl-ethynyl)-10,20-bis-[4-(octyloxy)phenyl]-porphinato}-zinc(ii) (), is reported. Their photophysical properties were studied by steady-state absorption and emission. Substituting the carbazolylethynyl moieties at two of the meso positions results in a large bathochromic shift of all the absorption bands, a notable increase in the absorption coefficient of the Q(0,0) band, and higher fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Porphyrins (containing metal-free porphyrins and metalloporphyrins), which play irreplaceable roles in organisms such as photosynthesis and oxygen transport, are receiving constant attention because of their unique optoelectronic properties; , the delocalized π electrons endow them with outstanding performances in numerous domains. Recently, expanded porphyrins, reported by Stuyver et al, were excellent candidates for molecular switches in molecular electronic devices, mainly attributed to their high combination density, fast response, and high energy efficiency . Zhang et al reported that the conversion efficiency of solar cells could be significantly improved in the presence of zinc­(II) 5,10,15,20-tetraethynylporphyrin as a core and perylene diimide as end groups .…”
mentioning
confidence: 99%
“…Porphyrins (containing metal-free porphyrins and metalloporphyrins), which play irreplaceable roles in organisms such as photosynthesis and oxygen transport, are receiving constant attention because of their unique optoelectronic properties; , the delocalized π electrons endow them with outstanding performances in numerous domains. Recently, expanded porphyrins, reported by Stuyver et al, were excellent candidates for molecular switches in molecular electronic devices, mainly attributed to their high combination density, fast response, and high energy efficiency . Zhang et al reported that the conversion efficiency of solar cells could be significantly improved in the presence of zinc­(II) 5,10,15,20-tetraethynylporphyrin as a core and perylene diimide as end groups .…”
mentioning
confidence: 99%
“…Taken together, the two reduction peaks are ascribed to the [H]­P · – → [H] 2 P 2– and Zn 2+ P → Zn + P in such organic conditions. , Also, the oxygen dissolved into the DCM/TBAP system can be reduced to O 2 – , which integrates with the ZnP to display noticeable ECL emission by the coreactant-energized pathway . The ECL mechanism can be illuminated as follows , …”
Section: Results and Discussionmentioning
confidence: 96%
“…42,43 Also, the oxygen dissolved into the DCM/ TBAP system can be reduced to O 2 − , which integrates with the ZnP to display noticeable ECL emission by the coreactantenergized pathway. 19 The ECL mechanism can be illuminated as follows 43,44 Zn P e Zn P (at 1.41 V)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The desired alkyne‐carrying photoredox catalyst was synthesised analogue to the well‐established emitter 4CzIPN. Starting from 3‐bromo‐9 H ‐carbazole, the protected alkyne moiety was introduced by a Sonogashira coupling with ethynyltrimethylsilane following the literature protocol to obtain 3‐((trimethylsilyl)ethynyl)‐9 H ‐carbazole 2 with a good yield of 72 % [10] . The protecting TMS‐group on the alkyne moiety is necessary for the construction of the clickable photocatalyst, based on previously reported methods, by substitution of 2,4,5,6‐tetrafluoroisophthalonitrile with the deprotonated carbazole [7b] .…”
Section: Resultsmentioning
confidence: 99%
“…Starting from 3-bromo-9H-carbazole, the protected alkyne moiety was introduced by a Sonogashira coupling with ethynyltrimethylsilane following the literature protocol to obtain 3-((trimethylsilyl)ethynyl)-9H-carbazole 2 with a good yield of 72 %. [10] The protecting TMS-group on the alkyne moiety is necessary for the construction of the clickable photocatalyst, based on previously reported methods, by substitution of 2,4,5,6-tetrafluoroisophthalonitrile with the deprotonated carbazole. [7b] After fluoride mediated deprotection of the four TMS-groups, the photocatalyst 4EthynylCzIPN 3 was obtained with an excellent yield of 97 % over two steps (Scheme 1).…”
Section: Synthesismentioning
confidence: 99%